2020
DOI: 10.3390/s20154315
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Analysis of Bicycle Sharing Systems as Public Transport Systems Based on a Trip Index Classification

Abstract: Bicycle Sharing Systems (BSSs) are exponentially increasing in the urban mobility sector. They are traditionally conceived as a last-mile complement to the public transport system. In this paper, we demonstrate that BSSs can be seen as a public transport system in their own right. To do so, we build a mathematical framework for the classification of BSS trips. Using trajectory information, we create the trip index, which characterizes the intrinsic purpose of the use of BSS as transport or leisure. The constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Still on short distance traffic, [ 17 ] proposed a solution to the issue of bicycle sharing systems (BSSs), which are traditionally conceived as a last-mile complement to the public transport system. The paper demonstrated that BSSs can be seen as a public transport system in their own right and built a mathematical framework for the classification of BSS trips.…”
Section: Analytics and Predictionmentioning
confidence: 99%
“…Still on short distance traffic, [ 17 ] proposed a solution to the issue of bicycle sharing systems (BSSs), which are traditionally conceived as a last-mile complement to the public transport system. The paper demonstrated that BSSs can be seen as a public transport system in their own right and built a mathematical framework for the classification of BSS trips.…”
Section: Analytics and Predictionmentioning
confidence: 99%